A microfluidic gradient device for drug screening with human iPSC-derived motoneurons. Issue 8 (9th March 2020) - Mo, Sung Joon; Lee, Ju-Hyun; Kye, Hyeon Gi; Lee, Jong Min; Kim, Eun-Joong; Geum, Dongho; Sun, Woong; Chung, Bong Geun
Abstract : We developed a microfluidic gradient device to utilize as a drug screening system with human induced pluripotent stem cell (hiPSC)-derived motoneurons. Abstract : We developed a microfluidic gradient device to utilize as a drug screening system with human induced pluripotent stem cell (hiPSC)-derived motoneurons. The microfluidic channel was asymmetrically designed to generate the concentration gradients and a micropillar array was used to trap and culture the motoneuron spheroids containing motoneurons for 9 days. We optimized the concentration gradients in the microfluidic device using a computational fluid dynamics (CFD) model. We also observed that the motoneuron spheroid-derived neurite network was generated in response to the concentration gradients of riluzole in the microfluidic device. Therefore, this microfluidic gradient device could be useful for screening of various drugs for neurological disease applications.